Sustaining Breastfeeding Practice at BFHI: A Review - Addenan, Nor Ashikin; Muda, Siti Mariam; Ibrahim, Amirah Fatin (International Journal of Human and Health Sciences (IJHHS), 2024)
Introduction: BFHI is a global effort to encourage and recognize hospitals and birthing centers that offer an optimal level of care for infant feeding and mother-baby bonding, launched by the WHO and UNICEF in 1991. At the heart of BFHI is the concept of the “Ten Steps to Successful Breastfeeding.” These steps provide a framework for hospitals to ensure that they offer effective support to mothers and their babies in initiating and sustaining breastfeeding. The breastfeeding practices implemented in the hospital focusing to increase mother’s education and implementation during the accreditation of BFHI. The purpose of this review is to find the articles related to breastfeeding intervention and support through BFHI accreditation in the hospital setting and to evaluate the breastfeeding intervention towards an implementation of BFHI globally. Methods: The online database used in this review is from ProQuest and Scopus. Inclusion criteria outlined in the table of reference with objectives, study designs, settings & participants, interventions & outcomes. Results: A total of 67 selected articles related breastfeeding intervention and support through BFHI across the world. Patterns identified were: i) Barriers and strategies for BFHI implementation in hospital setting; ii) Intervention promoting exclusive breastfeeding; iii) Health worker breastfeeding knowledge and training needs strengthening to ensure long term modification in breastfeeding practice; iv) Educational intervention programmes for pregnant and postpartum mothers are essential for continuous exclusive breastfeeding. Conclusion: The value of this review indicates the intervention and education programmes toward successful breastfeeding journey and giving benefits to hospital to provide continuous training and education to the health care workers. The implications of this study will enhance the sustainability of right breastfeeding method implemented by postnatal mothers. International Journal of Human and Health Sciences Supplementary Issue 02: 2024 Page: S25